Union Planning: A Framework and Research Agenda - Devine, Kay; Reshef, Yonatan (Relations industrielles / Industrial Relations, 1996)
Planning is fondamental to all organizations, including unions. This paper presents a research framework and discusses future directions of academic research into union planning. Our findings indicate that union planning is manifested in various forms. Further, we propose that to capture the phenomenon adequately, researchers must approach it from a "union context", rather than building solely upon a management, economics or business policy framework.